2019
DOI: 10.2139/ssrn.3433389
|View full text |Cite
|
Sign up to set email alerts
|

The Scope of Audit Committee Oversight and Financial Reporting Reliability: Are Audit Committees Overloaded?

Abstract: Audit committee (AC) responsibilities have been increasing over time, prompting concerns that overloading ACs may impair their effectiveness. Using new measures to capture AC responsibilities based on AC charters, we find that greater AC responsibilities are associated with improved financial statement reliability. Contrary to overload concerns, this association is strongest when ACs have very high levels of responsibilities. Cross-sectional analyses indicate greater AC responsibilities improve financial state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…In general, there is broad-based evidence that AC independence and expertise are associated with many different control, audit, and reporting outcomes (e.g., Klein 2002;Abbott, Parker, and Peters 2004;Krishnan 2005;Cohen et al 2014). 9 Despite the difficulty in measuring AC authority and diligence, some studies have shown that these dimensions also affect financial reporting quality (e.g., Badolato, Donelson, and Ege 2014;Ashraf, Choudhary, and Jaggi 2020;Bratten, Causholli, and Sulcaj 2019). 10 My study relates closely to the resources component of AC effectiveness.…”
Section: Audit Committeesmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, there is broad-based evidence that AC independence and expertise are associated with many different control, audit, and reporting outcomes (e.g., Klein 2002;Abbott, Parker, and Peters 2004;Krishnan 2005;Cohen et al 2014). 9 Despite the difficulty in measuring AC authority and diligence, some studies have shown that these dimensions also affect financial reporting quality (e.g., Badolato, Donelson, and Ege 2014;Ashraf, Choudhary, and Jaggi 2020;Bratten, Causholli, and Sulcaj 2019). 10 My study relates closely to the resources component of AC effectiveness.…”
Section: Audit Committeesmentioning
confidence: 99%
“…Anecdotally, three AC chairs I interviewed confirmed without exception that they are careful to carry out every duty listed in their charter. Thus, I consider the AC charter a useful proxy for actual AC responsibilities and activities (Ashraf et al 2020).…”
Section: Measurement Of Iaf-related Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, with increasing responsibilities of audit committee members, serving on multiple audit committees may well overburden the directors concerned and exacerbate the problem of information overload (Ashraf et al, 2020). Service on the audit committee involves a higher meeting frequency (Brandes et al, 2016), and greater responsibilities with respect to the management of financial risks (Vera‐Munoz, 2005), than is the case with any other mandatory committee.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…We first investigate the effect of the financial expertise of the audit committee. The responsibilities of the audit committee have been ever-expanding (Ashraf et al, 2019). Since the audit committee oversees the financial reporting process and is directly responsible for the appointment, and oversight of the work of the external auditor, management's desire to engage in auditor shopping may face resistance from a diligent audit committee.…”
Section: The Effect Of Monitoring On Auditor Shoppingmentioning
confidence: 99%